Faktor-Faktor yang Mempengaruhi Sisa Hasil Usaha Koperasi Syariah Masjid di Bandung - Nafisah Yuliani; Roosdiana Roosdiana; Siti Aisyah (STIE Indonesia Banking School, 2017)
The purpose of this research is (1) to identify the factors that influence the rest of the result of sharia mosque cooperative business in Bandung, (2) To describe the implementation of sharia system to acquire SHU in sharia cooperative mosque in Bandung. The object of research is ten sharia co-operative mosque in Bandung which already have legal body and active in its operational activity. The research variables consist of independent variables (X1: number of cooperative members, X2: business volume, X3: amount of deposits, X4: total debt) and dependent variable (residual result of SHU). Sharia cooperative performance is measured by: Capital Ratio, Efficiency Ratio, Liquidity Ratio, Independence Rate Ratio and Cooperative Growth followed by regression and correlation analysis between independent and dependent variable. Quantitative performance analysis results show the average capital ratio, efficiency ratio, profitability, service operational independence from 2010 to 2012 increased. The liquidity ratio shows the capability of the sharia mosque cooperative in fulfilling its short-term obligations in 2010-2011 just in time. The results showed that business volume factors (X2) and the amount of debt (X4) had a dominant influence in SHU formation in Shariah cooperative mosque in Bandung City. Implementation of Sharia System on the acquisition of SHU in Sharia Cooperative Mosque in Bandung City has shown complied with the calculation of sharia pattern in accordance with the Decree of State Minister of Cooperatives and Small and Medium Business Dam. 91 /KEP / M.KUKM / IX / 2004. Sharia co-operative mosque in Bandung city applies instrument in developing people economy through syariah financing instrument in the form of mudharabah, murabahah instrument, musyarakah instrument, giving training on syariah cooperative, sacrificial saving, holiday saving, service.